NEEDLE EXCHANGE PROGRAMS TO REDUCE THE SPREAD OF HEPATITIS C. - Seham Fayadh Eid Alanazi, Registered Nurse (Chelonian Research Foundation, 2024)
Needle exchange programs have been implemented as a harm reduction strategy to reduce the spread of blood-borne infections, such as hepatitis C, among injection drug users. This essay explores the effectiveness of needle exchange programs in reducing the transmission of hepatitis C. Through a review of the literature and analysis of relevant research studies, it will be demonstrated that needle exchange programs play a crucial role in preventing the spread of hepatitis C among at-risk populations. The methodology involves a comprehensive search of academic databases and reputable journals to gather evidence supporting the positive impact of needle exchange programs. The discussion will focus on the key findings of the research, highlighting the benefits of needle exchange programs in reducing the incidence of hepatitis C and improving public health outcomes. In conclusion, the essay will assert that needle exchange programs are a valuable tool in combating the spread of hepatitis C and should be supported as part of a comprehensive public health strategy.